Bioinformatics analysis of pyroptosis-related differentially expressed genes in sepsis and diabetes mellitus - Mengxuan Liu; Haiyan Song; Can Zhang; Jiaxin Li; Meng Han; Ying Li (PLoS ONE, 2026)
Sepsis and diabetes mellitus (DM) are major global health issues with high morbidity and mortality, necessitating new molecular insights for improved treatments. In this study, pyroptosis-related differentially expressed genes (PRDEGs) linked to both diseases were identified through bioinformatics analyses of GEO datasets (GSE28750 and GSE55098). These analyses included differential expression analysis, GO/KEGG pathway enrichment, gene set enrichment analysis (GSEA), protein-protein interaction (PPI) network construction, and peripheral blood immune cell composition analysis. Seven PRDEGs ( GZMA, GZMB, MMP9, LCN2, ANXA3, PRF1, and CAMP ) were identified, involved primarily in cytolysis and the IL-17 signaling pathway. GSEA indicated transcriptional changes in the IL-12 signaling pathway. PPI analysis identified key hub genes related to sepsis and DM, and immune cell composition analysis revealed correlations between immune cells and PRDEGs. These findings indicate that the identified PRDEGs are closely associated with both sepsis and DM, suggesting their potential as molecular markers for future research into shared mechanisms underlying the two diseases.